Analisis Penerapan Capital Asset Pricing Model dalam Pengambilan Keputusan Investasi Saham di Jakarta Islamic Index 70 - Ilham, Muhamad Arifin; Kalimah, Siti (JIOSE: Journal of Indonesian Sharia Economics, 2025)
This study aims to analyze stock investment decision-making using the Capital Asset Pricing Model (CAPM) method. The research population includes all companies listed in the Jakarta Islamic Index 70 (JII70). The sampling technique used is purposive sampling. The results of the study show that there are 24 stocks included in the efficient stock group, namely ADRO, AKRA, ANTM, BMTR, BRIS, BTPS, CTRA, ERAA, EXCL, INCO, ISAT, ITMG, KLBF, LPPF, MAPI, MIKA, MNCN, PTPP, PWON, SIDO, SMRA, TLKM, TPIA, and UNTR. The recommended investment decision for investors is to buy stocks that are classified as efficient. On the other hand, there are 11 stocks that are included in the group of inefficient stocks, namely ACES, CPIN, ICBP, INDF, INTP, JPFA, MYOR, PTBA, SCMA, SMGR, and UNVR. For these inefficient stocks, the recommended investment decision is to sell the stocks to avoid potential depreciation.